Interacting with academic readings — A comparison of paper and laptop - Nanna Inie; Louise Barkhuus; Claus Brabrand (Social Sciences and Humanities Open, 2021)
Academic reading, a form of active reading, often involves interaction with the text. Highlighting and annotating are some of the most common strategies of interacting with academic texts, yet we have limited understanding of exactly how such interactions affect reading comprehension in digital versus analog reading environments. In this paper, we present an exploratory study, comparing how university students (n = 50) interact with a digital and a physical text, focusing on highlights and annotations. We compare reading time, interaction with, and subsequent memory of the texts. We make nine observations about reading time, highlighting and annotation frequency and memory scores between paper and laptop. We find that students annotate significantly less on laptop than on paper, but that neither highlighting nor annotations influence subsequent memory of the text in either condition. Our broader contribution is to augment understanding of how different interaction features aid academic reading in a natural environment.